(untitled) (Research, Society and Development, 2022)
The growing demand for food makes agribusiness an impressive sector in the Brazilian and world economy. But despite this vigorous growth over the years, the agribusiness supply chain faces constant risks of disruption due to the inherent challenges of food and fruit culture. The objective of this research was to identify and describe the preeminent risks of rupture in the açaí supply chain, from the perspective of managers of companies in the State of Pará that works with extraction, processing, commercialization, and support to managers of companies that work with açaí. The methodological approach applied was qualitative research through multiple case studies using semi-structured interviews. As a result, this research developed a framework with 22 risks of disruption in the food supply chain, consolidated into 13 groups. The evidence analysis demonstrated a high vulnerability in the açaí supply chain, since all the risks mapped applies to the açaí chain, except for the risk related to antibiotic/agro toxic and demand. It was also possible to identify that managers are aware of the vulnerability of the açaí supply chain but do not use any risk management method or process.